SUNDAY SCHOOL TEACHER SERVICE STRATEGY FOR CHILDREN'S SPIRITUAL GROWTH DURING THE COVID-19 PANDEMIC - Lupmotis Amelia Sitompul; Sutrisno Sutrisno; Christiani Hutabarat (Didache: Jurnal Teologi dan Pendidikan Kristen, 2022)
There are many factors that can affect a child's spiritual growth, such as the role of parents, the environment, and Christian religious education teachers both at school and in the church. One of the topics discussed in this article is the role of the Sunday School teacher in the life of a child. Therefore, the teacher must have several abilities that can later complement the children. They are spiritual and have a good understanding of the Bible, but they are also very creative when it comes to serving children. However, the current obstacle in the Sunday School section is the strategy for serving children according to the situation and conditions during the COVID-19 pandemic. Because strategy is very important so that Sunday School children continue to worship God during the pandemic. Some of the strategies that will be discussed in this article are both online and onsite. However, this strategy also has drawbacks. This article offers several strategies to help teachers stay enthusiastic about serving and Sunday School children grow in their faith during the COVID-19 pandemic.